(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The development of tourism in Georgia and its individual regions depends on the potential of the tourism resources possessed by this or that region. The potential of tourism resources is largely determined by geographic and climatic factors.The Kakheti region has great prospects for the development of almost all types of tourism, which puts on the agenda the need to assess climatic factors that contribute or hinder the effective use of tourism potential.The table presented in the article shows that the tourism potential of the Kakheti region is characterized by favorable conditions due to climatic factors. The annual time of sunshine is quite long, the number of sunny days is frequent, the average annual air temperature is high, and the number of days without precipitation is frequent, which contributes to the rational and effective use of these factors in all types of tourism.